Factors Affecting Infant Formula Feeding in Infants Aged 0-6 Months in Sukoharjo, Central Java - Nuralita, Ayunda Yonik; Murti, Bhisma; Pamungkasari, Eti Poncorini (Journal of Maternal and Child Health, 2017)
Background: Formula feeding in infants aged 0-6 months may increase the risk of morbidity and mortality. Formula feeding in Indonesia continues to increase from 15% in 2003 to 79.8% in 2013. To the best of the authors